Physical and Chemical Characteristic Analysis of Liquid Organic Fertilizer from Chicken Manure and Mustard Greens Waste - Rista Delyani; Jaini Fakhrudin; Muhammad Ali; Lisnawati Waruwu; Putriana Putriana (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Liquid organic fertilizer (LOF) can be made from organic waste. The purpose of this study was to determine the physical and chemical characteristics of liquid organic fertilizer made from chicken manure and mustard green waste. This study used a Completely Randomized Design with 5 treatments of combinations of the amount of mustard green waste and chicken manure as follows: P1: Chicken manure 1000 g, P2: Mustard green waste 750 g, P3 Chicken manure 500 g + Mustard green waste 500 g, P4: Chicken manure 250 g + Mustard green waste 750 g and P5: Chicken manure 750 g + Mustard green waste 250 g. The results showed that in 45 days the LOF produced had the following physical characteristics: temperature ranging between 27-29.38 °C, foul-smelling aroma, and color varying from yellowish green to black. In addition, the chemical characteristics were as follows: pH values ranged from 5.53 - 7.96, the content of macro nutrients (N + P2O5 + K2O) ranged from 0.2-0.8% and C-organic was between 0.5-0.8%. Most of the character did not meet the minimum technical requirements by the Ministry of Agriculture Decree number 261 of 2019. Further studies are required to determine better composition of organic matters.